One‐year follow up of contraceptive use and pregnancy rates after early medical abortion: Secondary outcomes from a randomized controlled trial of immediate post‐abortion placement of intrauterine devices - Sara Hogmark; Niklas Envall; Kristina Gemzell‐Danielsson; Helena Kopp Kallner (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Intrauterine devices (IUDs) effectively prevent unwanted pregnancies. Little is known about long‐term outcomes of women choosing an IUD after early medical abortion. Material and methods We present secondary outcome data of continuation rates, factors associated with continuation and discontinuation, choice of IUD type, women's satisfaction with IUD, and IUD expulsions, subsequent pregnancies, and abortions within 1 year post‐abortion in a randomized, controlled, multicenter trial on IUD placement within 48 hours compared with placement 2–4 weeks after medical abortion up to 63 days’ gestation (ClinicalTrials.gov NCT03603145). Results Of the 240 women studied, 112/120 (93.3%) in the intervention group vs 113/120 (94.2%) in the control group completed the 12‐month follow‐up. The rate of IUD use at 12 months was 84/112 (75%) in the intervention group vs 75/113 (66.4%) in the control group (P = 0.19). Attendance at the IUD placement visit was the only predictor of long‐term IUD use (relative risk [RR] = 5.7, 95% confidence interval [CI] 2.03–16.0; P = 0.001). The main reason for choosing an IUD was high contraceptive effectiveness. The most common reasons for IUD discontinuation were bleeding problems and abdominal pain. IUD expulsion was rare and did not differ between groups. Satisfaction among IUD users at 1 year was high (>94%) and the majority of all participants would recommend IUD to a friend (65.8%). Use of no contraception and experience of unprotected intercourse were less common in the intervention group (11/112 [9.8%] vs 25/113 [22.1%], P = 0.02 and 17/112 [15.2%] vs 32/113 [28.3%], P = 0.02, respectively). There was no difference in the rate of subsequent pregnancies and abortions (pregnancies 14/112, 12.5% in the intervention group vs 8/113, 7.1% in the control group, P = 0.19; abortions 5/112, 4.5% vs 3/113, 2.7%, P = 0.5). Conclusions IUD placement after medical abortion led to high continuation and satisfaction rates with no difference between groups. We found no difference in IUD expulsions after immediate compared with later placement. Unprotected intercourse was significantly less common in the immediate group. In clinical practice, immediate placement of IUDs available free of charge at the abortion clinic is likely to increase attendance to the placement visit and continued use of IUDs after abortion.